CATEGORY SHIFT OF NOUN PHRASES IN TRANSLATING FIVE LITTLE PIGS NOVEL BY AGATHA CHRISTIE - Yanti, Ni Wayan Kristina; Winarta, Ida Bagus Gde Nova; Permana, I Putu Andri (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The purposes of this study are to identify the kinds of category shift and describe how the principles of translation occurs in the translation of noun phrase in Five Little Pigs novel. In this study the data was taken from a novel by Agatha Christie (1942) entitled Five Little Pigs as the source language and its translated version in Indonesian entitled Mengungkit Pembunuhan as the target language. The data were collected by using observation method and combine with note taking method to find out and classify the data. The theory used in analyzing the data ware a theory of Category Shift proposed by Catford (1965) and a theory of principles of translation by Nida (1975). Descriptive qualitative method was used to analyze the data. The findings of this study demonstrate that all kinds of category shifts were discovered in the novel's translation of noun phrases. The most frequent data found was the structure shift consisting of 155 data or 49.3%. The second is unit shift that has 108 data or 34.3%, the third was class shift which reach the number of 31 data or 9.8%. And the last is intra-system shift consisting 20 data or 6.3% percentages out of the total data were 314 data. Moreover, for the principles of translation, the highest frequency found is gain of information with 139 data or 44% out of 314 data. Then, loss of information with 110 data or 35% and skewing of information that has 65 data or 20%. Keywords: Translation, Category shift, Principles of translation, Noun phrase, Novel